Análisis de las condiciones jurídicas, sociales y laborales de acuerdo a normativa, acción internacional y legislación ecuatoriana para la eliminación de las peores formas de trabajo de niñas, niños y adolescentes - Álvarez Terán, David Alejandro (2011)
Labor exploitation of children is defined as any form of labor exploitation and economic hindrance to the integrated development of children and attacks against the interests of the same, thereby endangering their safety, physical and psychological health and education.Labor exploitation of children and adolescents violate human rights promulgated to them, is because of this reason all the necessary decoupling of children of all economic activity be it paid or unpaid. The economic needs of Ecuadorian families who are in poverty are the reasons that promote child labor from an early age, who must survive on the streets of our country without social security for children under fifteen years, ever since age will directly influence standards prohibitive when there are extreme financial need. Another reason for linking children and adolescents is cultural work, as there are still beliefs that promote job training early positive children. Family businesses are, likewise, sources that promote child labor as cheap labor or even free, with no recognition of any compensation. The purpose of this thesis is an analysis of national and international standards that affect the states social policy to promote the eradication of Labor minors in order to sensitize the public and protect our countrys foundation for future who are the children and return its infancy. The aim with this thesis provides solutions to this social problem, with the aim that no child or adolescent should be free education, recreation and family protection and State. In the legal field, it requires respect for the laws prohibiting the exploitation of child labor and impose sanctions on individuals, which should be a state policy to emphasize that the authorities in compliance with the principle of "best interests of child ".